Pengembangan Media Pembelajaran Berbasis Website Mata Pelajaran Matematika untuk Siswa Madrasah Ibtidaiyah - Ilma Almaida Fasa; Kristi Liani Purwanti (Universitas Negeri Malang, 2023)
The purpose of this research is to develop internet-based learning media and examine the viability of using website learning media to generate materials for class VI mathematical subjects such as prisms, cylinders, pyramids, cones, and spheres. The ADDIE Research and Development (RnD) paradigm (analysis, design, development, implementation, and evaluation) was employed for the research. Two validators, media specialists and material experts, conducted the feasibility test. Ten pupils from class VI C MI Nashrul Fajar Semarang participated in the trial. The result of media experts validation is in valid category with 4.5 point, material experts validation showed an extremely valid result at 4.75, and trials field gets a high agreements level at 4.34. As a final result, the products resulting from this research are considered very valid so that they are suitable for use and students are interested in the appearance of this website's learning media. Tujuan penelitian ini adalah mengembangkan media pembelajaran berbasis internet dan mengkaji kelayakan penggunaan media pembelajaran website untuk menghasilkan materi mata pelajaran matematika kelas VI seperti prisma, silinder, limas, kerucut, dan bola. Paradigma Penelitian dan Pengembangan (RnD) ADDIE (analysis, design, development, implementation, dan evaluation) digunakan untuk penelitian ini. Uji kelayakan dilakukan oleh dua orang validator yaitu ahli media dan ahli materi. Sepuluh siswa dari kelas VI C MI Nashrul Fajar Semarang mengikuti uji coba tersebut. Uji tuntas pada ahli media menghasilkan temuan sangat valid sebesar 4,5, uji tuntas pada ahli materi menghasilkan hasil sangat valid sebesar 4,75, dan uji coba menghasilkan skor sangat setuju dengan skor 4,34. Hasilnya, produk yang dihasilkan dari penelitian ini dinilai sangat valid sehingga layak digunakan dan siswa tertarik dengan tampilan media pembelajaran website ini.